ANALISIS PENGARUH ROA, ROE, NPL, DAN LDR TERHADAP CAR DI PERBANKAN INDONESIA PERIODE 2004-2015 - Gladis Kusuma Jaya (Jurnal Ekonomi dan Bisnis, 2016)
This research aims to analyze whether the Return On Asset (ROA), Return On Equity (ROE), Non Performing Loan (NPL) and Loan to Deposit Ratio (LDR) have significantinfluencesimultaneously and partially toward Capital Adequacy Ratio (CAR). This research classifiedthe verificativeresearch. The population is the national private commercial bank period 2004-2015. Sample was determined by the higher bank asset, a total of fivecompanies. The secondary data were taken such as from financialreport of Banks started from 2004 until 2013. The technique of data analysis in this research using panel regresion analysis. CAR as a dependent variable, ROA, ROE, NPL and LDR as independent variables. Data processing using Eviews 6. The result provides evidance that ROA, ROE, NPL, and LDR have significantinfluencesimultaneously toward CAR. ROA and NPL partially have positive significantinfluencetoward CAR. ROE and LDR partially have negative significantinfluencetoward CAR.